Forest industries in South American countries - Carlos Bacha (European Regional Science Association (ERSA), 2002)
This paper analyzes the performance of forest industries in South American countries. Special attention is given to the relationships that exist between the evolution of forest industries and the exploitation of natural and planted forest as well as on the role of national governments in stimulating that kind of industries. South America has large natural forest areas and excellent natural conditions for planting trees. However, forest industries have not grown in a way that permit sustainable exploitation of natural forests and improve the Gross National Product and Trade Balance of South America's countries. This paper suggests how the latter can be done better.
Keywords: 330